INCREASE ENTREPRENEUR MOTIVATION OF STUDENTS THROUGH GUIDANCE CAREER - Ridwan, Aam; Tijanul, Aziz; Falah, Noor; Sodikin, Sodikin (EDUCATIONE, 2023)
The aims of this study were to (1) determine the effectiveness of life skill-based career guidance services in problem solving techniques in increasing entrepreneurship among students; (2) to find out how students are motivated to become entrepreneurs after being given life skills-based career guidance services; (3) To find out whether there is an effect of life skill-based career guidance services to increase students' entrepreneurship motivation; (4) To find out whether life skill-based career guidance services are effective in increasing the entrepreneurial motivation of students. This study uses a qualitative-quantitative approach by examining data based on random sampling with a population of students at Islamic boarding school al-Ilham, Bandung district. The steps to determine the effectiveness of career guidance for students were carried out 5 times with 1 posttest test without a control group. In general, the stages of this research include: (1) Observation (2) data collection (3) data analysis using the T-test with the independent sample T-Test (t-test) formula and the use of SPSS software. The results of data analysis using the Independent Sample t-test formula using the help of SPSS showed that there was an effective life skills-based career guidance to improve student entrepreneurship at Al-Ilham Islamic Boarding School. The increase in the average data obtained from the control class and the experimental class. The control class pretest data showed an average score of 89, the experimental class with an average score of 114 with a difference of 25 and an increase in the positive direction.